VALUE-BASED MARKETING TRANSFORMATION IN ISLAMIC HIGHER EDUCATION: A MULTIDIMENSIONAL ANALYSIS OF COMPETITIVE DEVELOPMENT STRATEGIES, BRAND IMAGE, AND TRANSFORMATIVE STUDENT EXPERIENCES - Mulyono, Hardi; Fikri, Muhammad Hilman; Hadian, Arief; Panjaitan, Dedi Juliandri; Syamsuri, Abd. Rasyid (LPPM Universitas Jambi, 2025)
This study analyzed the marketing strategies of Islamic universities in North Sumatra in strengthening institutional competitiveness through a quantitative approach using structural equation modeling (SEM). A total of 125 respondents participated, and the findings revealed that brand image (0.401), value-based marketing strategy (0.321), and service quality (0.276) significantly contributed to university competitiveness. Mediation analysis further showed that student transformative experience provided a strategic pathway, with notable contributions from brand image (0.356), marketing strategy (0.287), and service quality (0.242). These results underscore that creating meaningful student experiences serves as a critical driver in enhancing the competitive positioning of higher education institutions. The novelty of this study lies in developing a conceptual framework that explicitly integrates marketing strategies with the Islamic spiritual context, thereby challenging the traditional paradigm that views higher education marketing solely from a transactional or utilitarian perspective. By embedding spiritual and value-based principles into branding and service quality, the framework highlights how Islamic universities can differentiate themselves in an increasingly competitive global academic landscape. Practically, the study provides a strategic blueprint for university management, encompassing value-based branding, innovative communication, enhanced service quality, and the cultivation of transformative student experiences. Beyond producing intellectually capable graduates, the findings stress the importance of nurturing individuals who are spiritually grounded and adaptable to global change. This integrative approach positions Islamic universities not only as centers of academic excellence but also as institutions of character formation and moral leadership in society.